2015
DOI: 10.1002/jmri.25046
|View full text |Cite
|
Sign up to set email alerts
|

Age-independent myocardial infarct quantification by signal intensity percent infarct mapping in swine

Abstract: Purpose To test whether signal intensity percent infarct mapping (SI-PIM) accurately determines the size of myocardial infarct (MI) regardless of its age. Materials and methods Forty-five swine with reperfused MI underwent 1.5T late gadolinium enhancement (LGE) MRI after bolus injection of 0.2mmol/kg Gd(DTPA) on days 2-62 following MI. Animals were classified into acute, healing, and healed groups by pathology. Infarct volume (IV) and infarct fraction (IF) were determined using binary techniques (including 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…4,10,12 While lower binary thresholds (2, 3, and 4SD) have been found to be inaccurate for MI quantification in previous investigations with pathologic validation, higher cutoffs (5 and 6SD, and FWHM) are generally considered more accurate when compared to the binary TTC method. 4,10,12 While lower binary thresholds (2, 3, and 4SD) have been found to be inaccurate for MI quantification in previous investigations with pathologic validation, higher cutoffs (5 and 6SD, and FWHM) are generally considered more accurate when compared to the binary TTC method.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…4,10,12 While lower binary thresholds (2, 3, and 4SD) have been found to be inaccurate for MI quantification in previous investigations with pathologic validation, higher cutoffs (5 and 6SD, and FWHM) are generally considered more accurate when compared to the binary TTC method. 4,10,12 While lower binary thresholds (2, 3, and 4SD) have been found to be inaccurate for MI quantification in previous investigations with pathologic validation, higher cutoffs (5 and 6SD, and FWHM) are generally considered more accurate when compared to the binary TTC method.…”
Section: Discussionmentioning
confidence: 94%
“…Our findings showed that MI quantification with nonbinary PIM LGE and PIM T1 leads to significantly lower IV and IF values compared to binary techniques, which is in line with previous animal studies. 4,10,12 While lower binary thresholds (2, 3, and 4SD) have been found to be inaccurate for MI quantification in previous investigations with pathologic validation, higher cutoffs (5 and 6SD, and FWHM) are generally considered more accurate when compared to the binary TTC method. [17][18][19][20] However, it is important to emphasize that the lower IV and IF by PIM LGE and PIM T1 was an expected finding.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations